CURRENT REALITIES OF PRE-EDUCATION TRAINING UNDER THE CONDITIONS OF MARTIAL LAW - Trehub , Mykola; Pashchenko , Oleksandr; Medvedovska , Tetyana; Skachko , Larisa (Collection of scientific papers «ΛΌГOΣ», 2023)
The department of pre-university training is a structural subdivision of the Interbranch Institute of Continuing Education, Full-time and Distance Education of the Dnipro University of Technology. This department carries out educational and career guidance work related to the preparation of applicants for admission to higher education institutions.